ANALISIS KESEJAHTERAAN ANGGOTA KOPERASI (STUDI KASUS PADA KOPERASI LKM SIDO JAYA ABADI) - Laila, Shofiyany; Lestari, Diah Aring Hepiana; Situmorang, Suriaty (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
This research aims to (1) analyze the utilization of the business unit of the LKM Sido Jaya Abadi Cooperative in terms of members’ savings and loans, as well as the economic benefits received through profit-sharing (SHU); (2) the welfare level of cooperative members; and (3) the factors influencing their welfare. The study was conducted at the LKM Sido Jaya Abadi Cooperative with a sample of 96 members. Data were analyzed using descriptive qualitative methods for cooperative utilization and SHU value, Sajogyo’s criteria for welfare level assessment, and multiple linear regression to identify factors affecting welfare. The results showed that the average savings deposited by members was Rp1,070,833, the average loan received was Rp4,125,000, and the average SHU received was Rp31,417. According to Sajogyo’s criteria, most members were in the “sufficient” welfare category. Additionally, farm size and crop commodity had a positive effect on welfare, while the number of family members had a negative effect. Key words: expenses, prosperity of members, SHU